2021
DOI: 10.1111/pai.13442
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of fixed low‐dose oral immunotherapy for children with severe cow’s milk allergy

Abstract: Cow's milk (CM) allergy, one of the major food allergies with a prevalence of 2%-3%, 1,2 accounts for 21% of food-induced anaphylaxis in the UK. 3 In Japan, CM is the second most common cause of food allergy in children. Although about 50%-90% of children with childhood-onset CM allergy acquire tolerance by school age, 4,5 children with severe CM allergy that have high CM-specific immunoglobulin E (sIgE) levels and a history of anaphylaxis often have persistent CM allergy. 4,6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 29 publications
(38 reference statements)
1
40
0
Order By: Relevance
“…This indicated that there were similarities in milk sIgE patterns among patients with persistent milk allergy and those in other milk OIT long‐term study 15,21 6–11,14,15,22,23 . In addition to the current knowledge, we showed that the immunological responses related to milk OIT varied between the outcome groups and that the sIgG4 levels should be evaluated with sIgG4/IgE ratio.…”
Section: Discussionsupporting
confidence: 55%
“…This indicated that there were similarities in milk sIgE patterns among patients with persistent milk allergy and those in other milk OIT long‐term study 15,21 6–11,14,15,22,23 . In addition to the current knowledge, we showed that the immunological responses related to milk OIT varied between the outcome groups and that the sIgG4 levels should be evaluated with sIgG4/IgE ratio.…”
Section: Discussionsupporting
confidence: 55%
“…Miura et al reported the outcome of fixed dosing for milk OIT at 1,2,3 years. 131 Children with severe milk allergy received a fixed dose of only 3ml daily with OFC to 25ml each year with 27%, 52%, and 61% achieving this goal. Baseline sIgE levels predicted this success and participants showed significant reduction in sIgE to casein with increased milk and casein specific IgG4.…”
Section: Updates On Clinical Treatment Approachesmentioning
confidence: 99%
“…SU is undoubtedly a more desired but also more uncertain outcome. Data are (relatively) more robust for SU to peanut than for milk or egg OIT, though study protocol variability makes comparison difficult 10,36–47 . Chinthrajah et al demonstrated a progressive loss of tolerance over a year of avoidance following 2 years of peanut OIT, providing valuable data on the potentially transient nature of SU 41 .…”
Section: Importance Of Including Efficacy and Effectiveness Outcomes ...mentioning
confidence: 99%